2018
DOI: 10.1016/j.margeo.2017.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Weathering fluxes and sediment provenance on the SW Scottish shelf during the last deglaciation

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 100 publications
0
8
0
Order By: Relevance
“…The dating of these glacial and glacially derived landforms and sediments provides key datasets to support a more refined chronological reconstruction of the behaviour of the two ice streams during the last glaciation (Arosio et al ., 2018a; Callard et al ., 2018; Ó Cofaigh et al ., 2019; Tarlati et al ., 2020). Constraining a maximum extent of the BIIS across the Malin Sea has not been straightforward due to the presence of intense iceberg turbation at the shelf edge in correspondence with the margin of the MSIS at the shelf edge.…”
Section: Results and Interpretationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The dating of these glacial and glacially derived landforms and sediments provides key datasets to support a more refined chronological reconstruction of the behaviour of the two ice streams during the last glaciation (Arosio et al ., 2018a; Callard et al ., 2018; Ó Cofaigh et al ., 2019; Tarlati et al ., 2020). Constraining a maximum extent of the BIIS across the Malin Sea has not been straightforward due to the presence of intense iceberg turbation at the shelf edge in correspondence with the margin of the MSIS at the shelf edge.…”
Section: Results and Interpretationsmentioning
confidence: 99%
“…This is a pattern of retreat observed commonly in marine‐based palaeo‐ice streams (Ottesen et al ., 2005; Shaw et al ., 2006; Larter et al ., 2009; Winsborrow et al ., 2010; Jakobsson et al ., 2012; Newton and Huuse, 2017; Bradwell et al ., 2021). Between 21 and 15.4 ka, the reduction in the flux of subglacially derived material, measured using radiogenic Pb isotope data, to the continental shelf is interpreted as the result of the break‐up of the ice‐stream in western Scotland (Arosio et al ., 2018a) and glaciomarine conditions are still indicated in the shelf sediments around the Scottish coastline (Callard et al ., 2018). Sedimentological evidence from the Donegal‐Barra Fan suggests some marine extension of the BIIS until as late as ~16.5 ka that allowed glaciomarine sediment deposition on the fan, with discrete episodes of calving recorded as peaks in IRD between 18 and ~16.5 ka (Tarlati et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of 23 BRITICE‐CHRONO publications report on new dates and their stratigraphic and glaciological contexts, and then build regional reconstructions of the glacial history of the various regions (Peters et al ., 2016; Sejrup et al ., 2016; Arosio et al ., 2018; Small et al ., 2017a, 2018; Evans et al ., 2017, 2018a,b; Smedley et al ., 2017a; Bateman et al ., 2018; Callard et al ., 2018, 2020; Roberts et al . 2018a,b, 2020; Chiverrell et al .…”
Section: The Britice‐chrono Projectmentioning
confidence: 99%
“…Pilot analyses of tills, debris flow deposits, diamictons, and glacimarine sediments delivered by specific ice streams from different peri‐North Atlantic ice sheets have confirmed that their inorganic characteristics reflect that of closely adjacent basement rocks and revealed that they are able to distinguish between most of these individual glacigenic depocenters (Farmer et al, 2003; Hemming et al, 2002; Verplanck et al, 2009). The use of the inorganic fingerprints of such ice‐proximal glacigenic deposits in a few recent IRD provenance studies, so far only conducted at the scale of individual ice sheets or individual ice streams, has further refined the origin of some IRD‐rich layers and/or further constrained the spatiotemporal retreat dynamics of single ice streams (e.g., Arosio et al, 2018; Jennings et al, 2017; Pierce et al, 2014; Rashid et al, 2012; Roy et al, 2009; Scourse et al, 2000; Verplanck et al, 2009). Combined together, these studies attest to the great potential of such IRD source archives to track individual source ice streams at the scale of a whole ocean basin.…”
Section: Introductionmentioning
confidence: 99%